The Brazilian national dam safety information system (SNISB) - Portela, E. A. (2015)
Many countries have enacted dam safety laws at the national level and have been applying them to dam safety management activities. In Brazil, the first Dam Safety Regulation was published in 2010. The National Dam Safety Information System (SNISB, by its Portuguese acronym) is an instrument of the Brazilian National Dam Safety Policy (PNSB), which was established by the Federal Law nº 12.334/2010. The SNISB consists of a system for collecting, processing, storing and recovering information related to dams under construction, in operation and decommissioned. The main purpose of SNISB is to inform about the safety conditions of regulated dams across the country and to allow the follow-up of the advances in the implementation of the PNSB. Its basic principles are the decentralization of data and information production and input; unified coordination of the system and access to information guaranteed to whole society. The main features of SNISB include the support for implementing the PNSB; the interaction with existing systems at ANA; the exchange of information with dam owners; the follow up activities from regulators and the support for the production of the annual Dam Safety Report. The responsibility for keeping the information available in SNISB system belongs to the regulating entities, either federal or state, which are responsible for ensuring that dam owners comply with the dam safety regulations. Dam owners will be the main source of information to the system. Besides being a federal regulating agency, the National Water Agency (ANA) is also the system manager.